Pemanfaatan Air Limbah Domestik Kegiatan Hotel X untuk Penyiraman Ruang Terbuka Hijau - Ihlashulamal, Tiyan; Okik Hendriyanto Cahyonugroho (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The tourism sector, particularly hotel operations, generates domestic wastewater in significant quantities concurrent with high consumption of fresh water. This study analyzes the potential utilization of treated wastewater from Hotel X for green open space irrigation and non-potable applications. The research was conducted using secondary data from the Technical Approval Document of Hotel X (2025), employing a descriptive quantitative approach. The fresh water demand was determined to be 79.72 m³/day, with wastewater generation of 62.07 m³/day, and GOS area of 1,792 m². The domestic wastewater of Hotel X comprises 81.5% greywater and 18.4% blackwater, treated through a wastewater treatment plant (WWTP) system consisting of grease trap, equalization tank, aeration tank, clarifier, sludge tank, and chlorination unit. The treated effluent meets the standards stipulated in Government Regulation No. 22 of 2021. Wastewater utilization encompasses green open space irrigation (23.97 m³/day) and toilet/urinal flushing (38.19 m³/day), achieving a utilization efficiency of 99.86%. Results demonstrate that treated wastewater can effectively substitute fresh water for non-potable uses, thereby promoting sustainable water resource management and reducing fresh water dependency in hotel operations.